Uptake of Cervical Cancer Screening Services and Associated Factors among HIV Positive Women in Central Uganda: A cross-sectional study. - Namuyiga, Edna Mirembe; Mukaga , Humphreys; Nakitende, Shamim; Kigongo, Edith; Ejalu , David Livingstone (Student’s Journal of Health Research Africa, 2024)
Background The main objective of the study was to identify the factors associated with the uptake of cervical cancer screening services among HIV-positive women at Mukono General Hospital, a high-volume facility in Central Uganda. Methods A cross-sectional study design was used, and quantitative data was collected from 417 HIV patients attending Mukono General Hospital. Systematic random sampling was used, and data was collected using interviewer-administered questionnaires. Modified Poisson regression analysis was used to identify the significance associated with the uptake of CCS at 95% confidence. Results The average age of study respondents was 34.4 years with the majority 63.5% (265/417) married and 86.4% (360/417) having a non-detectable viral load. Slightly more than a third 38.6% (161/417) reported having carried out CCS, of which 76.4% (123/161) did it within the last 3 years. Predictors associated with CCS included being of Basoga tribe [APR=1.27, CI=1.07-1.51, P=0.007], Perceiving that CC is curable [APR=0.68, CI=0.48-0.96, P=0.031], believing to be at risk of contracting [APR=3.08, CI=1.94-10.09, P=0.045], having a peer diagnosed with CC [APR=1.14, CI=1.08-1.34, P=0.03], perceiving that screening procedure was nasty [APR=0.70, CI=0.58-0.85, P<0.001], learning about CCS from media [APR=0.074, CI=0.54-0.01, P=0.047] and rating health workers as being professional [APR=2.59, CI=1.23-5.46, P=0.01]. Conclusion There was generally a low uptake of CCS among HIV/AIDS patients. Strategies to increase the uptake of CCS among the study population should hinge on addressing the knowledge gap and negative perceptions among HIV patients. Recommendation District health authorities should conduct regular awareness creation campaigns, targeting HIV-positive women on CC preventive measures.